2018
DOI: 10.1038/s41598-018-35778-6
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Colombian Leishmania panamensis strains with different level of virulence

Abstract: The establishment of Leishmania infection in mammalian hosts and the subsequent manifestation of clinical symptoms require internalization into macrophages, immune evasion and parasite survival and replication. Although many of the genes involved in these processes have been described, the genetic and genomic variability associated to differences in virulence is largely unknown. Here we present the genomic variation of four Leishmania (Viannia) panamensis strains exhibiting different levels of virulence in BAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 106 publications
(107 reference statements)
0
25
0
Order By: Relevance
“…Another interesting finding was associated with the 225 SNPs annotated, shared between the three clades analyzed ( Figure 5A,B. Table S4), most of them previously described in the literature and involved in the different biological processes of the parasite [27,68].…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Another interesting finding was associated with the 225 SNPs annotated, shared between the three clades analyzed ( Figure 5A,B. Table S4), most of them previously described in the literature and involved in the different biological processes of the parasite [27,68].…”
Section: Discussionmentioning
confidence: 77%
“…Despite these findings, we analyzed the genes with CNVs and observed that 44 of them were shared among all the genomes. Interestingly, some of them have been previously identified by other authors and include genes involved in parasite survival and virulence [27,28], which indicate their importance during the adaptation to human hosts. Additionally, the ontology enrichment analysis revealed that most genes with CNVs were involved in cellular ion zinc homeostasis in many clinical isolates; some of these genes were previously identified in L. infantum [63], as reported by a previous study, wherein the authors have described the need of these genes in the parasite to maintain the intracellular concentrations of zinc and avoid the toxic effects of this metal.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations